1994
DOI: 10.1103/physrevb.50.12015
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and geometrical structure of rutile surfaces

Abstract: The periodic Hartree-Fock approach is used in all-electron calculations on bulk rutile (Ti02) and various slabs modeling the (001), (100), and (110) surface to study possible geometric and electronic surface relaxations, convergence of properties with slab thickness, and the relative stability of the different surfaces. Results are discussed by means of a Mulliken population analysis, band structures, and the density of states. We find displacements of surface atoms ranging from 5 to nearly 40 pm; the (001) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
47
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(60 citation statements)
references
References 32 publications
12
47
1
Order By: Relevance
“…In Table I, a summary of the results from a selection of experimental and recent ab initio studies of the structural parameters of rutile and anatase is presented. Early HF, 57,58 PW-LDA, [59][60][61][62] and combined HF and DFT studies of rutile 63 yielded lattice parameters to within 2% of experiment. More recent studies that have taken advantage of improvements in the theoretical techniques and available computing power to perform calculations with improved treatments of exchange and correlation ͑DFT calculations based on the GGA͒ ͑Refs.…”
Section: Resultsmentioning
confidence: 99%
“…In Table I, a summary of the results from a selection of experimental and recent ab initio studies of the structural parameters of rutile and anatase is presented. Early HF, 57,58 PW-LDA, [59][60][61][62] and combined HF and DFT studies of rutile 63 yielded lattice parameters to within 2% of experiment. More recent studies that have taken advantage of improvements in the theoretical techniques and available computing power to perform calculations with improved treatments of exchange and correlation ͑DFT calculations based on the GGA͒ ͑Refs.…”
Section: Resultsmentioning
confidence: 99%
“…We note that a recent study using HF theory on a nine layer ͑100͒ slab found the displacement of the surface oxygen to be Ϫ0.39 Å in the ͓010͔ direction and 0.04 Å along the ͓100͔ direction. 25 In this study only the surface oxygen plane was relaxed. Repeating our relaxation ͑using the TVAE basis set͒ but fixing the positions of all the atoms except for the surface oxygen layer, we find similar displacements of Ϫ0.39 Å along the ͓010͔ direction and 0.06 Å in the ͓100͔ direction.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies of the relaxation of the (100)-(1 ϫ1) surface have been performed within the local-density approximation ͑LDA͒ to DFT using the plane-wave pseudopotential technique 12,24 ͑PW-LDA͒ and also within the HF approximation 25 using an all-electron local basis set formalism. The results of these calculations are, at best, in qualitative agreement.…”
Section: Introductionmentioning
confidence: 99%
“…The first picture consists in the decomposition of the CuF 2 structure into stoichiometric one-dimensional CuF 2 chains formed by lineconnected CuF 4 units, the basal planes of the coordination octahedra. [28][29][30][31] These one-dimensional chains follow the Cu 1 -Cu 3 line in Fig. 1.…”
Section: The Cuf 2 Crystalmentioning
confidence: 98%